Combination of photothermal, prodrug and tumor cell camouflage technologies for triple-negative breast cancer treatment - Zhang Lirong; Ma Xiaodong; Zhou Wenhui; Wu Qiwei; Yan Jiaqi; Xu Xiaoyu; Ghimire Bhawana; Rosenholm Jessica M; Feng Jing; Wang Dongqing; Zhang Hongbo (ELSEVIER, 2022)
Triple-negative breast cancer (TNBC) remains the most challenging breast cancer subtype. In the presented work, we have combined several emerging technologies to build up a nanoplatform for TNBC treatment: photothermal therapy, prodrug design and tumor cell camouflage formulation. First, we synthesized a paclitaxel (PTX) based prodrug PTX-SS, and then conjugated it to the surface of gold nanorod (Au NR) @ mesoporous silica (MSN) core-shell nanoparticles (Au@MSN-NH2 NPs). Subsequently, doxorubicin (DOX) was loaded into the Au@PTXSS-MSN NPs and further coated with cell membranes isolated from MDA-MB-231 cells to form cell camouflaged Au@PTXSS-MSN/DOX@CM NPs. The Au@PTXSS-MSN/DOX@CM NPs exhibited very good DOX loading capacity and the prodrug strategy enabled the precise adjustability of PTX-SS loading to achieve the optimized ratio between PTX and DOX to maximize the synergistic effect of these two drugs, as well as enabled GSH-responsive intracellular drug release. More interestingly, the cell membrane coating not only protected the drug from premature release, but also significantly improved the targeting ability of NPs to breast cancer MDA-MB-231 cells. The NPs also showed good photothermal responsiveness with clear improvement in inhibiting MDA-MB231 cell proliferation under laser irradiation. The in vivo studies further confirmed the effectiveness of Au@PTXSS-MSN/DOX@CM NPs on TNBC tumor inhibition in 4T1 cell grafted tumor mice model. (c) 2021 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/).